ANALISIS PENERAPAN JUST IN TIME TERHADAP PENINGKATAN KUALITAS PRODUK DAN EFISIENSI BIAYA PADA PT. SAWITA PASAMAN JAYA PASAMAN BARAT - Zakiatur Rahmi; Musfiari Haridhi (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
This study aims to analyze the application of the Just In Time method to improving product quality and cost efficiency at PT SPJ. Pasaman Barat. This study used descriptive qualitative method. The data used are primary data and secondary data. Primary data using interview techniques, literature study, and documentation. The results showed that (1) The application of the Just In Time method could improve product quality in terms of performance, reliability, conformance to specifications, durability and aesthetics. (2) The implementation of Just In Time can increase the efficiency of production costs, which is marked by the loss of ordering costs and raw material storage costs, the results obtained using the calculation of the manufacturing cycle efficiency formula of 82.93%, and the yield comparison of the amount of raw materials entering the company with the amount of CPO produced is 62.57%.